Apathy in Older Persons With Depression: Course and Predictors: The NESDO Study. (July 2016) - Groeneweg-Koolhoven, Isis; Comijs, Hannie C.; Naarding, Paul; de Waal, Margot W. M.; van der Mast, Roos C.
Objectives: Apathy is a common behavioral syndrome, influencing different areas of daily functioning and often seen in depression. Little is known about the course of apathy in depression. In this study, we examine the course and predicting factors of apathy in older persons with depression. Method: Data of 266 older persons with depression participating in the Netherlands Study of Depression in Older Persons, all aged at least 60 years with complete Apathy Scale scores at baseline and 2-year follow-up, were included in this study. Associations between several baseline variables and severity, incidence, and persistence of apathy were examined using regression analyses. Results: At 2-year follow-up, the severity of apathy was predicted by the severity of apathy at baseline, and incidence rate of apathy was 36%, with a lower baseline Mini-Mental State Examination score being an independent predictor. Older persons with incident apathy did not differ in remission rate of depression compared to those without apathy at follow-up. Persistence rate of apathy was 80% and was independently predicted by a higher baseline Apathy Scale score and, surprisingly, by less use of benzodiazepines. Persons with persistent apathy were less likely to recover from depression than those who remitted from apathy. Conclusion: Severity of apathy at baseline, but not depression, predicted apathy at follow-up. Incident apathy was predicted by poorer cognitive function, whereas severe apathy at baseline predicted its persistence. Remarkably, new apathy was not associated with worse outcome of depression whereas persistent apathy was.